Mitofilin Heterozygote Mice Display an Increase in Myocardial Injury and Inflammation after Ischemia/Reperfusion - Yansheng Feng; Abdulhafiz Imam Aliagan; Nathalie Tombo; Jean C. Bopassa (MDPI AG, 2023)
Mitochondrial inner membrane protein (Mitofilin/Mic60) is part of a big complex that constituent the mitochondrial inner membrane organizing system (MINOS), which plays a critical role in maintaining mitochondrial architecture and function. We recently showed that Mitofilin physically binds to Cyclophilin D, and disruption of this interaction promotes the opening of mitochondrial permeability transition pore (mPTP) and determines the extent of I/R injury. Here, we investigated whether Mitofilin knockout in the mouse enhances myocardial injury and inflammation after I/R injury. We found that full-body deletion (homozygote) of Mitofilin induces a lethal effect in the offspring and that a single allele expression of Mitofilin is sufficient to rescue the mouse phenotype in normal conditions. Using non-ischemic hearts from wild-type (WT) and Mitofilin+/− (HET) mice, we report that the mitochondria structure and calcium retention capacity (CRC) required to induce the opening of mPTP were similar in both groups. However, the levels of mitochondrial dynamics proteins involved in both fusion/fission, including MFN2, DRP1, and OPA1, were slightly reduced in Mitofilin+/− mice compared to WT. After I/R, the CRC and cardiac functional recovery were reduced while the mitochondria structure was more damaged, and myocardial infarct size was increased in Mitofilin+/− mice compared to WT. Mitofilin+/− mice exhibited an increase in the mtDNA release in the cytosol and ROS production, as well as dysregulated SLC25As (3, 5, 11, and 22) solute carrier function, compared to WT. In addition, Mitofilin+/− mice displayed an increase in the transcript of pro-inflammatory markers, including IL-6, ICAM, and TNF-α. These results suggest that Mitofilin knockdown induces mitochondrial cristae damage that promotes dysregulation of SLC25As solute carriers, leading to an increase in ROS production and reduction in CRC after I/R. These effects are associated with an increase in the mtDNA release into the cytosol, where it activates signaling cascades leading to nuclear transcription of pro-inflammatory cytokines that aggravate I/R injury.